Pseudo-exponentiation on algebraically closed fields of characteristic zero - Zilber, B (Elsevier, 2005)
We construct and study structures imitating the field of complex numbers with exponentiation. We give a natural, albeit non first-order, axiomatisation for the corresponding class of structures and prove that the class has a unique model in every uncountable cardinality. This gives grounds to conjecture that the unique model of cardinality continuum is isomorphic to the field of complex numbers with exponentiation. © 2004 Elsevier B.V. All rights reserved.